DESCRIPTION OF ANXIETY IN THE PATIENT'S FAMILY CAREGIVER SCHIZOPHRENIA IN THE COMMUNITY HEALTH CENTER OF MANYAR, GRESIK DISTRICT - Alghifahri, Sayyid Gaza; Rindayati, Rindayati; Makhfudli, Makhfudli; Lutfiandini, Cherlys Tin (Journal of Vocational Nursing, 2022)
Introduction: Schizophrenia is a disease process that affects perceptions, emotions, social behaviour and the ability to accept reality correctly. Caregivers with schizophrenia often feel anxious. This study aims to determine the description of anxiety in family caregivers of schizophrenia patients. Methods: This research is quantitative research with a descriptive approach. The number of respondents was 63 according to the inclusion and exclusion criteria. Using purposive sampling technique. This research was conducted at the Manyar District Health Center, Gresik Regency in March 2022. Processing and Data Analysis using Editing, coding, scoring, tabulating and percentages. In this study, the Hamilton Rating Scale for Anxiety ( HARS) questionnaire was used. Ethical Approval by the Faculty of Health, University Muhammadiyah of Gresik number 029/KET/II.3.UMG/KEP/A/2022, February 25, 2022. Results: The results of this study indicate the level of anxiety experienced by family caregivers of schizophrenic patients, that most of them experienced severe anxiety with many as 40 respondents (40.9%), a small proportion had no anxiety as many as 5 respondents (4.6%). Conclusions: Family caregivers who treat schizophrenia patients mostly experience mild anxiety. It is expected that the family caregiver can do distracted and deep breathing relaxation to reduce the level of anxiety experienced by the family caregiver.